Improving the Method of Forming a Set of Machines and Systems in the Construction of Residential Buildings (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The construction of residential buildings involves a complex integration of various machines and systems to ensure efficiency, safety, and cost-effectiveness. This study aims to improve the method of forming a set of machines and systems in the construction of residential buildings by analyzing current practices, identifying inefficiencies, and proposing a systematic framework. Findings reveal that traditional machinery selection and integration methods are predominantly based on empirical knowledge and supplier recommendations, leading to inefficiencies such as over-reliance on specific machines, lack of coordination, high downtime, and safety incidents. To address these issues, the study proposes a decision support system (DSS) for machinery selection, integration of Building Information Modeling (BIM), predictive maintenance systems, and enhanced training programs for operators. The proposed framework promises to enhance efficiency, reduce costs, and improve safety, though its implementation may face challenges including initial investment costs, industry resistance to change, and technical integration complexities. A critical evaluation of the framework underscores its potential benefits while addressing the obstacles that need to be overcome for successful adoption. This study provides a detailed analysis and offers practical recommendations for improving machinery and system integration in residential building construction, contributing to better project outcomes and industry practices. Future research should focus on developing detailed implementation guidelines and assessing the long-term impacts of the proposed framework on the construction industry.